Novas tecnologias na discursividade do ensino-aprendizagem de língua inglesa - Netto, Mônica Inês de Castro (2012)
This dissertation aims at presenting a research developed in the interface between Applied Linguistics and Discourse Analysis, considering the movement language-history-ideology which is trespassed by unconscious issues and by plurivocal manifestations that are constitutively dialogical. The aim was to analyze the discursivity about new technologies which is present in the scientific-institutional realm through the study of journals in the field of Applied Linguistics. The objective, throughout this study, was to have a picture of the linguistic traversals presented in the evaluated discursivity, trying to problematize the implications that these traversals bring to the context of new technologies use in the teaching-learning process taking into consideration that the focus was to unravel the discursive functioning, as well as to analyze the discursive construction and its impact, interrelating these crossings with the teachers´ practices in a classroom. I elected as my corpus ten scientific papers, related to the use of new technologies in the teaching-learning process of English, published in specialized journals of Applied Linguistics. In order to achieve my goals, I used as theoretical and methodological devices the Matrix Device developed by Santos (2004), according to which, through analytical-descriptive and interpretative matrixes, and from discursive sequences, it would be possible to select operating-utterances enunciative regularities present at the text and producers of meaning and from these enunciations constitute axioms, which according to Figueira (2007), emerge from these regularities and from their meaning effects. While mapping them, among the several discursive formations referring to the teaching-learning process through new technologies use, it was possible to establish that their insertion in the educational environment represents a direct impact in the English teaching-learning process. Certainly, new technologies substantially contribute to the actions of teachers and students, but the power which is discursively attributed to them, as if they could, by themselves, solve all the educational problems, does not contribute to the subject s taking position so that there could be relevant changes in the relation between the subjects who teach and learn and the way of teaching and learning languages. It was possible to observe, in the meanings aroused by the interpretation, that new technologies will be increasingly present in the teaching-learning process, but this presence is neither consistent with an immeasurable idolatry (technolatry) nor with a severe rejection to its use (technophobia). The interim place of these antagonistic discursivities seems to resound, in spite of the fact that we are in direction to the process of seeing new technologies as central in our lives, that there still is the problematization that by themselves new technologies in the teaching-learning process do not provoke changes and dislocations in the subjects positions. I believe that problematizing how the adoption of new technologies have been discursively produced in the teaching-learning process becomes relevant as it is possible to have a better understanding of the constitution, functioning, reception and distribution of discourses that constitute both the teaching-learning process of foreign languages and the education of pre and in-service teachers of these languages.